2002
DOI: 10.1002/sia.1188
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of CO2 and CO at fractional atmosphere pressures with iron and iron oxide surfaces: one possible mechanism for surface contamination?

Abstract: The interactions of carbon dioxide and carbon monoxide at moderately high pressures with clean iron surfaces have been studied using x-ray photoelectron spectroscopy (XPS) and static time-of-flight secondary ion mass spectrometry (ToF-SIMS). Clean iron surfaces were analysed after exposure to CO 2 or CO gas having pressures of 10-10 4 Pa at 25• C. Exposure to either gas results first in a thin surface film of FeO. In addition, this oxide is completely or partially covered with a carbonaceous layer. The thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
163
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(178 citation statements)
references
References 17 publications
15
163
0
Order By: Relevance
“…To begin, the binding energies (BEs) were adjusted for electrostatic charge buildup using the C1s peak from adventitious C-C/C-H. Whereas this adjustment is routine for clean metals and metal oxides, 64 the fitting of the C1s region will be discussed in detail because the present work examines graphite-based materials that contain organic binders (sodium carboxymethyl cellulose and styrene butadiene rubber) and that are predicted to have an organic SEI surface layer.…”
Section: Resultsmentioning
confidence: 99%
“…To begin, the binding energies (BEs) were adjusted for electrostatic charge buildup using the C1s peak from adventitious C-C/C-H. Whereas this adjustment is routine for clean metals and metal oxides, 64 the fitting of the C1s region will be discussed in detail because the present work examines graphite-based materials that contain organic binders (sodium carboxymethyl cellulose and styrene butadiene rubber) and that are predicted to have an organic SEI surface layer.…”
Section: Resultsmentioning
confidence: 99%
“…The process has an associated error of at least ±0.1 to ±0.2 eV. [19] Experience with numerous conducting samples and a routinely calibrated instrument have shown that the C 1s signal generally ranges from 284.7 eV to as high as 285.2 eV [M.C. Biesinger, unpublished results].…”
Section: Methodsmentioning
confidence: 99%
“…As the core levels of different chemical elements easily differ by tens to hundreds of electron-volts (eV), the peaks in the photoelectron distribution as a function of kinetic energy provide us with information on which chemical elements are present and, to a very good approximation, their relative abundance in a sample. When focusing on the photoelectron signals coming from one particular core level of one particular element, the different local environments around the targeted ions can result in a multi-peak structure, typically within an energy range of about 10 eV, from which the oxidation states of the probed element can be inferred [5][6][7]. A more sophisticated aspect of XPS is the electron screening due to the created core hole [3]: once a photoelectron is generated, the sample is left with a core hole (positively charged) that modifies the potential of valence electrons.…”
Section: Introductionmentioning
confidence: 99%